2012
DOI: 10.1111/jpm.12004
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement supports nurse workforce stability and quality of care: nursing team‐level analysis in psychiatric hospitals

Abstract: Research in healthcare settings reveals important links between work environment factors, burnout and organizational outcomes. Recently, research focuses on work engagement, the opposite (positive) pole from burnout. The current study investigated the relationship of nurse practice environment aspects and work engagement (vigour, dedication and absorption) to job outcomes and nurse-reported quality of care variables within teams using a multilevel design in psychiatric inpatient settings. Validated survey inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 50 publications
4
61
0
3
Order By: Relevance
“…, Othman & Nasurdin , Van Bogaert et al . ), whereas in other studies a relationship was only observed between social support and burnout (García‐Izquierdo & Ríos‐Rísquez , Ariapooran ). Although the results are consistent with previous literature, the hypothesis is only partly supported.…”
Section: Discussionmentioning
confidence: 81%
“…, Othman & Nasurdin , Van Bogaert et al . ), whereas in other studies a relationship was only observed between social support and burnout (García‐Izquierdo & Ríos‐Rísquez , Ariapooran ). Although the results are consistent with previous literature, the hypothesis is only partly supported.…”
Section: Discussionmentioning
confidence: 81%
“…Regarding the three dimensions of work engagement, dedication had the highest score, followed by absorption and vigor. Employees with high dedication and low vigor had relatively strong intention to turnover, especially when they also had heavy workload (Van Bogaert, Wouters, Willems, Mondelaers, & Clarke, ). Thus, the relatively low total score of work engagement and the lowest dimension of vigor might be of interest to nurse leaders.…”
Section: Discussionmentioning
confidence: 99%
“…patient mortality and complication rates in hospitals), organisational outcomes (profitability) and employees' health outcomes (nurses' physical and mental health) rather than job outcomes such as considering leaving the healthcare sector (Bargagliotti, 2012;Laschinger and Finegan, 2005;Simpson, 2009). Nevertheless, in their small-scale survey study including teams of nurses and non-registered caregivers in two psychiatric hospitals, Van Bogaert et al (2013) found that team work engagement is positively associated with intention to stay in the profession. Furthermore, Schaufeli and Bakker (2004) found a negative association between employees' work engagement and turnover intention among employees in a home-care organisation.…”
Section: Main Findingsmentioning
confidence: 95%